Analisis Kreativitas Siswa dalam Menyelesaikan Masalah Matematika Ditinjua Dari Kemampuan Awal Siswa - Lale Amrini Rosmala Dewi; Lia Puji Astuti; Marzela Faiza; Maudina Bunga Khairunisa (Griya Journal of Mathematics Education and Application, 2023)
This research is a quantitative study which is systematic literature review (SLR) method which can produce whether there is an influence between mathematical ability and creativity. This research use 20 articels. The purpose of this study is to describe creativity that influences the development of students in overcoming difficulties in problem solving activities. The results of the study were founs to show students’ creativity, namely fluency, flexibelty, novelty and elaboration.